Analysis of Service Quality at Regional Drinking Water Companies - Haedar Akib; Herlinda Herlinda; Herman Herman (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Public services, especially in the provision of clean water, require the principles of excellent service that is easy, cheap, friendly, accountable, precise and orderly. Continuous evaluation is necessary to ensure good service. This research aims to examine how to analyze service quality at the Regional Drinking Water Company in Tallo District, Makassar City. This type of research is qualitative using a descriptive approach. Data collection techniques were carried out by means of observation, interviews and documentation. The data analysis technique used consists of data condensation, data presentation and drawing conclusions. The research results show that the quality of service at the Regional Drinking Water Company in Tallo District, Makassar City can be determined from the timeliness of service, accuracy of service, politeness and friendliness, ease of obtaining service, comfort in obtaining service, service support attributes. Meanwhile, factors that influence the quality of service at the regional drinking water company in Tallo sub-district, Makassar City include: employee friendliness is considered to be still not good, parking is still haphazardly parked and the layout of the building is fairly complicated. The novelty of this research is that researchers can make a more significant contribution to understanding and improving the quality of PDAM services in Tallo subdistrict, Makassar City.